Estresse ocupacional e o consumo do álcool em trabalhadores hospitalares - Tuchtenhagen, Patrícia (2018)
Alcohol consumption is harmful not only to the person but to the family, the work environment and society. Work in the hospital environment can be stressful and for some workers the alcohol consumption can be a coping strategy. This study aims to evaluate the relationship between occupational stress and alcohol consumption by workers at a university hospital in the southern region of Brazil. This cross-sectional epidemiological study was carried out in 2018, with 815 workers. A questionnaire containing sociodemographic, labor and health data, the Alcohol Use Disorders Identification Test (AUDIT) and the Job Stress Scale (JSS) was used. The data were entered in Epiinfo and analyzed in the PASW, using descriptive and inferential analysis. The prevalence of alcohol consumption was 72.1%. Of these, 65% were classified into low-risk consumption, 5.8% in risk consumption, 0.3% in harmful consumption and 0.2% in consumption of probable dependence. As for work stress, 51% of the workers carried out activities with high psychological demand, 56.1% presented a high control in the work. Regarding social support, 54.8% have high social support. The combinations in the quadrants of the Demand-Control Model showed that 28.3% of workers are in active work and 22.7 in high demand. The highest odds for alcohol consumption are for male workers, 20-40 year old, graduates and postgraduates, who work in mixed shift, consumers of tobacco and that have a BMI < 25. It is concluded that the prevalence of alcohol consumption is high and probable low dependence. There was no significant association between alcohol and stress at work. Early screening is essential for the formulation of strategies, programs, surveillance and policies for actions to promote workers' health in relation to reducing alcohol consumption.